Reformulation of Corporate Liability Implementation in Money Laundering Crimes - Novian, Muhammad; Santoso, Topo; Nelson, Febby Mutiara (Journal of Law and Legal Reform, 2025)
Money laundering crimes (ML) are currently committed not only by individuals but also by corporations. The provisions of Money Laundering Crimes (MLC Law) regulate corporations, specifically Limited Liability Companies (PTs). However, since the enactment of MLC Law, only five legally binding rulings have involved corporations as perpetrators of ML offenses. In these rulings, there are several errors in the application of law. These errors include the fulfillment of the benefit element only being met when there is an increase in wealth, overlooking other circumstances such as a decrease in liabilities that the company must pay or use for its operations. Furthermore, in another ruling, the panel rejected the additional criminal charge of dissolving the corporation, with the legal reasoning that MLC Law does not regulate corporate dissolution. There are several rulings in which limited liability companies (PTs) were named as suspects but were ultimately found not guilty because the element of intent to conceal or disguise the origin of assets derived from criminal offenses was not fulfilled. This paper then compares several ML cases that occurred in the UK involving PTs, reflecting on some of these cases. In this paper, the author propose several ideas for the application of MLC Law, particularly for PTs involved in ML offenses. The methodology employed is doctrinal research. The paper emphasizes the necessity of optimizing sanctions against corporations that violate the MLC Law, not only in their capacity as perpetrators of money laundering but also for failing to fulfill obligations stipulated under the law.